2008
DOI: 10.4012/dmj.27.565
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Biofilm Formation using Newly Developed Coating Materials with Self-cleaning Properties

Abstract: The purpose of this study was to evaluate the inhibition of biofilm formation on newly developed coating materials with self-cleaning properties. A series of experimental coating materials containing fluoroalkylated acrylic acid oligomer (FAAO) were applied to resin composite substrates. The surfaces of the coating materials were analyzed by X-ray photoelectron spectroscopy (XPS) and contact angle measurement. Biofilm formation on the surface was assessed using Streptococcus mutans biofilms inside an oral simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 26 publications
3
39
0
3
Order By: Relevance
“…21,22,31 In addition, some in vitro studies on biofilm formation in an oral biofilm reactor (OBR) using cariogenic streptococci, primarily S. mutans and S. sobrinus, have repeatedly demonstrated the viability of these bacteria at low pH environment (lower than 4) when they remain active in a sucrose dependent glucan matrix. 25,26 As a single species, S. sobrinus has never demonstrated dominance over S. mutans in any clinical studies 32 ; the same trend was also observed in the present study. However, the current study showed that in the cavitated carious lesions, there was no correlation between pH value and either S. mutans or S. sobrinus.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…21,22,31 In addition, some in vitro studies on biofilm formation in an oral biofilm reactor (OBR) using cariogenic streptococci, primarily S. mutans and S. sobrinus, have repeatedly demonstrated the viability of these bacteria at low pH environment (lower than 4) when they remain active in a sucrose dependent glucan matrix. 25,26 As a single species, S. sobrinus has never demonstrated dominance over S. mutans in any clinical studies 32 ; the same trend was also observed in the present study. However, the current study showed that in the cavitated carious lesions, there was no correlation between pH value and either S. mutans or S. sobrinus.…”
Section: Discussionsupporting
confidence: 88%
“…Bacterial strains were cultured as described previously. 25,26 Genomic DNA was extracted and purified using a DNeasy tissue kit (QIAGEN) as mentioned above. The nucleic acid concentration was determined with a spectrophotometer (ND-1000, Nano-drop Technologies, Delaware, USA).…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Many techniques have been suggested for application to soft and hard surfaces, including silver or copper coated surfaces [20][21][22] , self-cleaning surfaces 23,24 and enzyme or bacteriophage immobilized surfaces 25,26 . In addition, the incorporation of light-activated antimicrobial agents (LAAAs) into surfaces is considered a promising technique [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gyo et al also evaluated the surface response of resin composites incorporated with a fluorine polymer in relation to inhibiting cariogenic biofilm adherence 39) . In continuance of this effort against biofilm adherence and formation, a newly developed coating material was investigated using an oral simulator and found to possess self-cleaning properties that inhibited biofilm adherence 40) . In light of these encouraging results and findings, it may be probable that a root surface coating material which embodies these properties would be developed and available in the near future: possesses good durability and wear resistance, and in particular prevents dentin demineralization and root caries formation.…”
Section: Discussionmentioning
confidence: 99%